2013
DOI: 10.1007/s00464-012-2686-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral chlorhexidine and microbial contamination during endoscopy: possible implications for transgastric surgery. A randomized, clinical trial

Abstract: Chlorhexidine mouth rinse was effective in reducing microbial contamination of the endoscope, but micro-organisms with abscess forming capabilities were still present. PPI treatment significantly increased CFU and should be discontinued before transgastric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Instead, we found a clear difference in the concentration of gastric bacteria in patients receiving and not receiving therapy and there were a significant number of samples that did not grow bacteria. Furthermore, a study by Donatsky et al 24 determined the change in bacteria concentrations in gastric fluid in adults who did and did not receive an oral decontaminant prior to endoscopy. They found that oral decontamination had no effect on gastric growth, suggesting that oral flora does not have an appreciable effect on gastric fluid flora obtained endoscopically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we found a clear difference in the concentration of gastric bacteria in patients receiving and not receiving therapy and there were a significant number of samples that did not grow bacteria. Furthermore, a study by Donatsky et al 24 determined the change in bacteria concentrations in gastric fluid in adults who did and did not receive an oral decontaminant prior to endoscopy. They found that oral decontamination had no effect on gastric growth, suggesting that oral flora does not have an appreciable effect on gastric fluid flora obtained endoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…They found that oral decontamination had no effect on gastric growth, suggesting that oral flora does not have an appreciable effect on gastric fluid flora obtained endoscopically. 24 Another limitation is that the channel of the scope was not sterile. However, Thorens et al, who collected gastric samples using a sterile tube with a distal rubber cap that was pierced at the time of endoscopy, identified a similar bacterial burden as we did despite different methods of collection.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine mouthrinse has been commonly used not only in dental practice but also in critical care to prevent ventilator-associated pneumonia [ 20 ]. Moreover, a previous RCT showed that chlorhexidine mouthrinse before gastroscopy was effective in reducing microbial contamination of the endoscope, resulting in an 88% reduction of the median CFU count of wash samples from the working channel of the endoscope [ 16 ]. In this context, we investigated the effect of chlorhexidine mouthrinse on the reduction of microbial contamination during EBUS-TBNA.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was estimated using the results obtained from an RCT of 100 patients who underwent gastroscopy with or without chlorhexidine mouthrinse [ 16 ] because previous studies on CFU counts of TBNA needle wash samples were not available. A sample size of 50 participants per group was required to evaluate whether chlorhexidine mouthrinse reduces the CFU counts of needle wash samples by 50% with an alpha of 0.05 and a power of 90%.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, antibiotic prophylaxis may be considered in high risk patients, such as in immunocompromised hosts or those with necrotizing, cystic, or calcified lesions, including hypovascular lesions. Gargling with chlorhexidine before the procedure might be also helpful in reducing the risk of bacterial adherence to EBUS-scope[ 14 ].…”
Section: Discussionmentioning
confidence: 99%